Rainwater- and air-driven 40 mm bladeless electromagnetic energy harvester - Zhao, Dan (2013)
A 40 mm electromagnetic energy harvester driven by both rainwater and air is designed and experimentally tested. Its performance is first assessed by measuring the system response for 4 different levels of air flow excitations. It shows that about 0.5 W power is generated. Parametric analysis is then conducted in terms of the disc number, exhaust flow rates, and the inter-disc distance. Finally, it is used to harness energy from rainwater. It is found the harvester works much better than the air-driven one. And its energy conversion efficiency is reduced with increased disc diameter. The maximum electric current is 4.5 mA.